1971
DOI: 10.1111/j.1432-1033.1971.tb01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Biosynthesis of Ubiquinones by Animals

Abstract: 1. Tissues of a number of avian and mammalian species have been examined for the presence of 2-polyprenylphenols7 6-methoxy-2-polyprenylphenols, 6-methoxy-2-polyprenyl-1,4-benzoquinones and 5-demethoxyubiquinones. I n no instance was evidence found of the presence of any of these compounds, although most tissues contained a t least two ubiquinones and one ubiquinol.2. Tracer studies with g~-hydroxy[U-~~C]benzoic acid have been carried out to detect the precursor of ubiquinone-9, "5-demethoxyubiquinone-9", repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…A quinone with the properties of a hydroxylated phylloquinone was also found in S. obliquus. 5'-Hydroxyphylloquinone has been identified in Euglena gracilis strain Z (Law et al, 1973) and a similar, and possibly identical, compound has been found in Anacystis nidulans and Chlorella pyrenoidosa (Henninger et al, 1965;Allen et al, 1967;Whistance & Threlfall, 1970b). The compound found in S. obliquus had chromatographic properties similar to those quoted by Law et al (1973), a u.v.…”
Section: Growth Of Scenedesmus Obliquus and Lipid Extractionmentioning
confidence: 68%
“…A quinone with the properties of a hydroxylated phylloquinone was also found in S. obliquus. 5'-Hydroxyphylloquinone has been identified in Euglena gracilis strain Z (Law et al, 1973) and a similar, and possibly identical, compound has been found in Anacystis nidulans and Chlorella pyrenoidosa (Henninger et al, 1965;Allen et al, 1967;Whistance & Threlfall, 1970b). The compound found in S. obliquus had chromatographic properties similar to those quoted by Law et al (1973), a u.v.…”
Section: Growth Of Scenedesmus Obliquus and Lipid Extractionmentioning
confidence: 68%
“…This method relies on the steady-state level of an intermediate being sufficiently high to allow its isolation and identification. Unfortunately, few intermediates in a pathway may be present in such quantities, and in some cases none of the intermediates may be detectable (17,26,28,29). Nevertheless, a number of polyprenylphe- The reactions affected by mutations in the various ubi genes are also shown.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the plastoquinone pool is large compared to that of the other electron carriers [1]. Homogentisic acid (2,5-dihydroxyphenylacetic acid) is the precursor for the aromatic moiety of the plastoquinone molecule from higher plants and from Anacystis nidulans, a cyanobacterium [2]. 4-Hydroxyphenylpyruvate dioxygenase [EC 1.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%